“Like the Windmills of Your Mind”: A Cross‐Country Investigation of the Role of Past Behavior in Circular Consumption Behavioral Intention - Lima, Pedro Augusto Bertucci [UNESP]; Badajoz‐Dávila, David; Luiz, Octaviano Rojas [UNESP]; Mariano, Enzo Barberio [UNESP]; Magnier, Lise (Wiley, 2025)
ABSTRACT Consumers are a fundamental link in closing material loops in the circular economy. However, the understanding of how past circular behaviors such as recycling and purchasing of recycled products are related to consumption intention (willingness to pay and choosing recycled products) of circular products is limited. Through a cross‐section online questionnaire with Brazilian ( N = 203) and Spanish ( N = 196) undergraduate students, this research employed Partial Least Square Structural Equation Modelling (PLS‐SEM) and multi‐group analysis to test the effect of past circular behavior on behavioral intention and the moderating effect of variables from an extended norm‐activation model (NAM) on this relationship. The findings indicate that past purchasing of recycled products is related to the intention of purchasing specific recycled products. However, past recycling behavior did not appear to be a good predictor of purchase intention. Despite the awareness of consequences, outcome efficacy, personal norms, social norms, and attitude present relationships with behavioral intention, the moderating effect of these variables was not consistently found. Our study contributes to existing literature by showing how variables from extended NAM models are good predictors of behavioral intention but not necessarily good moderator variables. The study innovates by showing that consumers already buying circular products tend to keep doing so, while efforts should be made to increase the spillover effect of recycling behavior into purchasing intention, as both are necessary to achieve the circular economy. Thus, policymakers, educators, and businesses should promote not only recycling but also circular purchasing through awareness, marketing, and norm‐shaping strategies.